Analisis Motivasi Sains Pada Pembelajaran Fisika Menggunakan Science Motivation Questionnaire (SMQ) II Pada Siswa Kelas X SMA/MA Di Kota Semarang - Putri, Dini Santika; Saptaningrum, Ernawati; Saefan, Joko (Jurnal Penelitian Pembelajaran Fisika, 2022)
This research aims to find out how the level of science motivation of students in the physics learning of class X high school in Semarang City using Science Motivation Questionnaire (SMQ) II. The data analysis method used in this study is quantitative descriptive analysis. The sample in this study was 357 students of class X in 15 of the 75 high schools in Semarang city with stratified random sampling technique. Online data collection techniques use questionnaires on google form and offline using questionnaires on paper. The results showed that the level of science motivation of students at class X high school Semarang city falls into the high category. In total, each component of science motivation has an insignificant score difference so that students' science motivation is almost evenly distributed in each component. The value motivation component had the highest score with 21,09% while intrinsic motivation scored the most with 19%. The self-efficacy component scored 19,94%, self-determination 19,96%, and career motivation 20,08%. The score obtained by each component is not much different between the components of science motivation. Motivation is included in the high category is one of the causes of the increase in the value of national exam high school at Semarang City in previous years.Keywords: science, science motivation, SMQ II